Highly active and durable self-standing WS2/graphene hybrid catalysts for the hydrogen evolution reaction. Issue 24 (1st June 2016) - Zhou, Haiqing; Yu, Fang; Sun, Jingying; He, Ran; Wang, Yumei; Guo, Chuan Fei; Wang, Feng; Lan, Yucheng; Ren, Zhifeng; Chen, Shuo
Abstract : Efficient hydrogen evolution catalysts are fabricated by growing WS2 on 3D graphene/Ni foam, featured by large current density (10 mA cm −2 at −119 mV) and low Tafel slope (∼43 mV per dec), outperforming most previous WS2 catalysts. Abstract : The development of three-dimensional (3D) efficient and earth-abundant electrocatalysts with good catalytic performance and long-term durability is desirable for the hydrogen evolution reaction (HER) in water splitting. Tungsten disulfide (WS2 ) has been long-pursued as a promising candidate, but the progress is slow, which is probably due to its poor electrical contact with the support and low density of active sites. Here we developed a highly active and stable WS2 catalyst for the HER by growing it into a 3D porous architecture on conducting graphene/Ni foam. The catalysts exhibit a ∼0.1 V overpotential, accompanied by a large cathode current density (10 mA cm −2 at −119 mV vs. reversible hydrogen electrode), a low Tafel slope of ∼43 mV per decade and good stability. The HER performance of WS2 catalysts is greatly improved, and is comparable to that of the well-known catalysts (MoS2, CoSe2, CoS2, etc. ), which benefits from the improved electrical conductivity of the WS2 catalysts by graphene and porous structures of the support. This work paves a new way to develop active and efficient WS2 -based catalysts for hydrogen generation.